2013
DOI: 10.1074/jbc.m112.449751
|View full text |Cite
|
Sign up to set email alerts
|

Ras Protein/cAMP-dependent Protein Kinase Signaling Is Negatively Regulated by a Deubiquitinating Enzyme, Ubp3, in Yeast

Abstract: Background: Ras proteins are important molecular switches. RasGAP is an essential negative regulator of Ras, and its activity is controlled by ubiquitination. Results: RasGAP interacts with a deubiquitinating enzyme, Ubp3. Disrupting Ubp3 activity leads to accumulation of ubiquitinated RasGAP and hyperactivation of Ras signaling. Conclusion: Appropriate deubiquitination of RasGAP by Ubp3 is important for Ras signaling. Significance: This study reveals a new layer of mechanism that regulates Ras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Recently, it was reported that cAMP levels are elevated in ubp3∆ mutants leading to hyper‐activation of the PKA signaling pathway and that overexpression of PDE2 , a phosphodiesterase that hydrolyzes cAMP, counteracts some phenotypes typical of cells lacking UBP3 (Li & Wang, ). Therefore, we tested whether overexpression of PDE2 could suppress the prolonged deposition of Ssa2‐GFP in JUNQ seen in ubp3∆ mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that cAMP levels are elevated in ubp3∆ mutants leading to hyper‐activation of the PKA signaling pathway and that overexpression of PDE2 , a phosphodiesterase that hydrolyzes cAMP, counteracts some phenotypes typical of cells lacking UBP3 (Li & Wang, ). Therefore, we tested whether overexpression of PDE2 could suppress the prolonged deposition of Ssa2‐GFP in JUNQ seen in ubp3∆ mutants.…”
Section: Resultsmentioning
confidence: 99%
“…UBP3 could deubiquitinate many different substrates. Indeed, previous studies have demonstrated roles for Ubp3 in enhancing or delaying the degradation of particular substrates by direct deubiquitination (Brew and Huffaker 2002;Cohen et al 2003a;Kraft et al 2008;Kvint et al 2008;Chew et al 2010;Li and Wang 2013). Ubp3 could also affect the proteasome itself.…”
Section: Discussionmentioning
confidence: 99%
“…Upon Ras1 activation, Ras1-GTP binds to AC and catalyzes production of the second messenger cAMP. Subsequently, the increase of intracellular cAMP activates cAMP-dependent PKA that phosphorylates a series of transcription factors that control phenotype, metabolism, stress adaption, proliferation, and other functions (Broach, 1991 ; Rolland et al, 2002 ; Cassola et al, 2004 ; Li and Wang, 2013 ). Further studies show that Efg1, a transcription factor, in parallel with other unidentified signaling molecules, is the terminal point of the Ras1-cAMP-PKA pathway in C. albicans (Bockmühl and Ernst, 2001 ; Shapiro et al, 2009 ).…”
Section: Potential Antifungal Targets Within Hsps-associated Intracelmentioning
confidence: 99%